Islam Membangun Masyarakat Bilateral dan Implikasinya terhadap Hukum Keluarga Islam Indonesia - Nasution, Khoiruddin (Al-Mawarid Jurnal Hukum Islam, 2007)
Oneaspect of Islam reform is the family system from patrhiarchal to parental system.The model of reform includesthree modelsnamely: deconsruction, reconstruction and that of continuity. And the methodof deconstruction in this context comprises of two kinds totally and step by step process. This article tries to investigate the family law based on bilateralsystem and that of principle and it is expected to apply in Indonesia.Besides, it also offer the role of Islamic law as not only as a social control but also as tool of social enginering.This article also tracesthe concept of family law both the conventional fiqh and the act of marriage in Indonesia as representing the gender bias. Kata kunci: Fiqh, hukum keluarga, pembaharuan, bilateral, dan undangundang.